2017
DOI: 10.1177/8755123317741489
|View full text |Cite
|
Sign up to set email alerts
|

Assessment in Music: A Practitioner Introduction to Assessing Students

Abstract: There has been an increased interest in documenting the growth and learning outcomes of students in all subjects in the past 20 years, and music education has not been immune to the accountability movement. Yet, in spite of the increased sociopolitical pressures put on educators, music has remained a difficult discipline to assess, which in turn has created tension between music educators and policymakers. This review of literature examines the basic nature of assessment in music education and discusses possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…The low perceived efficiency for group subjects could be explained by the fact that the online context limits the interpersonal experiences leading to a sense of loss of social connections due to the lack of socializing opportunities and joint music-making (Levstek et al, 2021). Although previous research has demonstrated the effectiveness of online teaching in the case of instrument lessons, or in terms of creative, group music activities (Pike and Shoemaker, 2013;Kruse, 2014;Denis, 2017), our study demonstrates that online music education is a necessary and useful tool, but it can also bring a series of risks. We believe that for individual instrument lessons or for practical courses in orchestra, choral ensemble or chamber music, online education can only be an additional, occasional form that can complement, not replace, the in-person forms of education, where students interact with each-other and with their teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low perceived efficiency for group subjects could be explained by the fact that the online context limits the interpersonal experiences leading to a sense of loss of social connections due to the lack of socializing opportunities and joint music-making (Levstek et al, 2021). Although previous research has demonstrated the effectiveness of online teaching in the case of instrument lessons, or in terms of creative, group music activities (Pike and Shoemaker, 2013;Kruse, 2014;Denis, 2017), our study demonstrates that online music education is a necessary and useful tool, but it can also bring a series of risks. We believe that for individual instrument lessons or for practical courses in orchestra, choral ensemble or chamber music, online education can only be an additional, occasional form that can complement, not replace, the in-person forms of education, where students interact with each-other and with their teachers.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of children's piano lessons conducted remotely via Skype and MIDI Internet, the rewards and challenges of three different approaches to distance learning were examined: synchronous (real time), asynchronous (real time) and a combination of synchronous with asynchronous. Thus, several benefits of such lessons have been reported, but it has been stated that practical problems related to technological complications may arise (Shoemaker and van Stam, 2010;Pike and Shoemaker, 2013;Kruse, 2014;Denis, 2017).…”
Section: Online Music Education During Covid 19 Pandemicmentioning
confidence: 99%
“…Vurdering beskrives som den mest kraftfulle enkeltkomponenten for laering i formell utdanning, i både positiv og negativ forstand. Positivt kan vurdering fremme laering og motivasjon, mens dårlig vurderingspraksis i verste fall kan underminere både innhold og tilnaerminger i undervisning (Boud et al, 1999;Denis, 2018). Til sammen danner dette et fruktbart bakteppe for å diskutere hvordan ØM fungerer, med tanke på både underveis-og sluttevaluering (karakterer).…”
Section: Tidligere Forskning Om Kvalitetsvurdering Av Kunstunclassified
“…It is worthy of note that assessment in music education has been a common topic of conversation for researchers (Denis, 2018;Fisher, 2008;Payne et al, 2019;Scott, 2012). Music educators, especially those in the basic schools in Ghana, have been faced with the pressures of increasing reliance on standardised assessment, including portfolio assessment schemes which have never worked for many years.…”
Section: Introductionmentioning
confidence: 99%